MULTILINGUALISM AND CLIL METHODOLOGY WITHIN MULTIED ERASMUS+ PROJECT - M. Zuyenko; V. Kravchenko; I. Kohut (Естетика і етика педагогічної дії)
The paper presents the results of a research into Ukrainian state and university language policies, and a Ukrainian university community’s potential to become multilingual in terms of its foreign language proficiency and attitudes toward multilingual educational approach. The article highlights the importance of multilingualism in modern society and the interdisciplinarity of its study as related to sociolinguistics, cognitive linguistics, and pedagogics. The results of the research prove that students understand the opportunities of foreign languages and ready to face new methods in teaching among them were relevantly presented storytelling as method of language teaching withing CLIL methodology. Ukrainian universities can develop their own multilingual models, as the case study of one top Ukrainian university (Poltava V.G. Korolenko National Pedagogical University) suggests.